Building Family Literacy Skills among Parents and Children in Developing Countries: An Impressionistic Account in Uganda - Magara, Elisam (My University, 2008)
Building family literary skills among parents and children will enable them to access and use information for national development. The existing literature reviewed shows that the three common approaches of family literacy include: the family and social life, home-school relationships, and the use of libraries and readership development. A descriptive, case study research design based in Kampala district, Uganda was conducted in all five divisions of the district to assess and establish the best approach for enabling parents and children to acquire family literacy skills in Uganda. In addition, published and unpublished documents regarding the subject, including information on children, families, education, community development, library development, and literacy were reviewed. Although the family and social life, the parent, school and teacher relationship, and libraries and readership development have been adopted in Uganda, there is lack of information access skills to ensure that parents and children acquire sustainable lifelong learning. In order to integrate information skills in the development of family literacy, parents are obliged to assume a leading role in developing and promoting the child’s social, educational and information needs. A family information literacy programme (FILP) will ensure that a child builds abilities of exploiting the available opportunities to access information for lifelong learning. The paper provides strategic directions for this programme that target increased access to information and books for parents and children to ensure the attainment of a literate and informed society.